Effects of capsicum oleoresin supplementation on rumen fermentation and microbial abundance under different temperature and dietary conditions in vitro - An, Zhigao; Luo, Gan; Abdelrahman, Mohamed; Riaz, Umair; Gao, Shanshan; Yao, Zhiqiu; Ye, Tingzhu; Lv, Haimiao; Zhao, Jvnwei; Chen, Changzhi; Yang, Liguo (Frontiers in Microbiology, 2022)
This study aimed to determine the effect of capsicum oleoresin (CAP) on rumen fermentation and microbial abundance under different temperature and dietary conditions in vitro. The experimental design was arranged in a 2 × 2 × 3 factorial format together with two temperatures (normal: 39°C; hyperthermal: 42°C), two forage/concentrate ratios (30:70; 70:30), and two CAP concentrations in the incubation fluid at 20 and 200 mg/L with a control group. Regarding the fermentation characteristics, high temperature reduced short-chain fatty acids (SCFA) production except for molar percentages of butyrate while increasing acetate-to-propionate ratio and ammonia concentration. The diets increased total SCFA, propionate, and ammonia concentrations while decreasing acetate percentage and acetate-to-propionate ratio. CAP reduced acetate percentage and acetate-to-propionate ratio. Under hyperthermal condition, CAP could reduce acetate percentage and increase acetate-to-propionate ratio, lessening the negative effect of high heat on SCFA. Hyperthermal condition and diet altered the relative abundance of microbial abundance in cellulose-degrading bacteria. CAP showed little effect on the microbial abundance which only increased Butyrivibrio fibrisolvens. Thus, CAP could improve rumen fermentation under different conditions, with plasticity in response to the ramp of different temperature and dietary conditions, although hardly affecting rumen microbial abundance.